1993
DOI: 10.1111/j.1476-5381.1993.tb13539.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium antagonistic and antiarrhythmic actions of CPU‐23, a substituted tetrahydroisoquinoline

Abstract: 1 The effects of (1-{1-[(6-methoxyl)-naphth-2-yl]}-propyl-2-(1-piperidine)-acetyl-6,7-dimethyoxy-1,2,3,4-tetra-hydroisoquinoline) were studied on mechanical and electrical activities, and intracellular free calcium ([Ca2+]i) of isolated cardiac tissues in order to investigate its spectrum and mechanisms of action in the heart. Its antiarrhythmic and haemodynamic effects in pentobarbitone-anaesthetized rats subjected to coronary artery ligation were also evaluated. 2 CPU-23 at 10-6 10-4 M markedly inhibited sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…As with previous studies in anaesthetized Sprague-Dawley (SD), spontaneously hypertensive (SHR) and normotensive (WKY) rats (Dong et al, 1992), CPU-23 lowered DBP and SBP; the decrease in SBP was short lived when compared to the decrease in DBP (Table 1). The haemodynamic pro®le of CPU-23 in vivo was consistent with our observations in vitro from cardiac tissue (Dong et al, 1993). Therefore we propose that the cardiodepressant eects of CPU-23 observed in the present study may be due in part to VGCC blockade.…”
Section: +supporting
confidence: 81%
See 1 more Smart Citation
“…As with previous studies in anaesthetized Sprague-Dawley (SD), spontaneously hypertensive (SHR) and normotensive (WKY) rats (Dong et al, 1992), CPU-23 lowered DBP and SBP; the decrease in SBP was short lived when compared to the decrease in DBP (Table 1). The haemodynamic pro®le of CPU-23 in vivo was consistent with our observations in vitro from cardiac tissue (Dong et al, 1993). Therefore we propose that the cardiodepressant eects of CPU-23 observed in the present study may be due in part to VGCC blockade.…”
Section: +supporting
confidence: 81%
“…In addition, CPU-23 inhibited KCl-induced Ca 2+ in¯ux and altered action potential characteristics of myocardial preparations. Consequently, we suggested that the cardiovascular eects of CPU-23 were due primarily to inhibition of calcium in¯ux via speci®c calcium channels, probably L-type VGCC (Dong et al, 1993). In the present study we have explored, in rat tail arterial rings, the mechanisms whereby CPU-23 induces either inhibition of KCl-and PE-induced contraction or vasodilation of a-adrenoceptor agonist-induced tone.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular myocytes of male adult Sprague-Dawley rats were isolated using a collagenase perfusion method, as described previously [17]. Immediately after a 60 min perfusion (60 min normal perfusion in the NC and NCEA groups and 10 min normal perfusion + 40 min low flow perfusion + 10 min normal reperfusion in the SGIR and EA groups), the heart was then continuously perfused at a constant flow of 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of isolated ventricular myocytes Single ventricular myocytes were prepared from the hearts of male Sprague-Dawley rats by enzymatic dissociation [10] . The heart was perfused using a Langendorff apparatus with a 100% oxygenated, non-recirculating Ca…”
Section: Methodsmentioning
confidence: 99%
“…Loading of cells with Fura-2/AM was carried out as described previously [10] . After stabilization, isolated myocytes were incubated with 1 mmol/L Fura-2/AM at room temperature for 30 min.…”
Section: +mentioning
confidence: 99%